66 Ultra-high density electroanatomic mapping and local impedance-guided ablation: a more accurate and efficient ablation strategy for cavotricuspid isthmus dependent atrial flutter?. (17th July 2020) - Saraf, Karan; Kumar, Narendra; Morris, Gwilym M
Abstract : Background: . Radiofrequency ablation (RFA) of CTI dependent atrial flutter (CTI-AFL) is conventionally performed under fluoroscopic guidance, or alternatively with 3D mapping and contact force (CF) catheters. Ultra-high density mapping (UHDm) and local impedance (LI) guided ablation have not yet been evaluated for this indication. Methods: . An observational study comparing conventional, CF and LI-guided ablation of CTI-AFL to understand whether LI offers superior ablation metrics and UHDm allows accurate identification of breakthrough after initial RFA. Retrospective analysis of consecutive CTI-AFL cases was performed. Irrigated RFA was used in all groups. Contact was determined in the CF group with target >9 g and in the LI group with patient-specific LI. Target LI drop of -20 ohms was used to determine effective lesion formation. Standard generator impedance was used for the conventional group. Power was limited to 40-50W in all groups. In the LI group, if the CTI was not blocked after initial ablation, UHDm was used to identify breakthrough. Mean RFA time, time to CTI block, number of lesions required to achieve block, acute procedural success and complications were analysed with ANOVA. Breakthrough points were manually assessed. Results: . Data is presented for 27 patients; 7 conventional, 10 CF and 10 LI. Mean RFA time was 6, 5.8, 3.2min respectively (p=0.0227). Significant differences also seen with LI vs Fluo (p=0.0194), LI vs CF (p=0.0164). Time from first application of RF to block was 22.8, 20.4, 14.2 min (p=ns). No significant difference was seen in the number of lesions required to achieve block. Acute procedural success was 100% in all groups, and there were no acute complications. Breakthrough was identified in 50% of CF and LI cases (5 patients in each group). With LI, there was one case of epicardial-endocardial breakthrough (EEB) 11mm from the CTI (figures A, B ), three posterior, and one anterior aspect of the CTI, identified with UHDm. Subsequent LI-guided RFA resulted in block, on average six minutes quicker vs CF. Discussion: This data illustrates that UHDm and LI-guided RFA significantly reduces the amount of ablation required (by 47% and 45% versus conventional and CF respectively; p=sig) by shortening lesion duration guided by LI change. A reduction from first RFA to block is also seen (47% and 30% respectively; p=ns). Many patients require further ablation following the initial RFA line, resulting in longer procedures. UHD mapping quickly and accurately identifies breakthrough for further focused RFA, including EEB away from the CTI which may otherwise be difficult to identify and treat using the conventional or standard 3D mapping, and result in prolonged procedure time and/or increased radiation exposure. LI also resulted in more predictable procedure times. We could not directly compare overall procedure times as many in the CF group had CTI combined with left atrial ablation. Conclusion: . LI-guided ablation is safe and effective, and has shown favourable ablation metrics when compared with conventional and CF-guided ablation for CTI dependent AFL. Ultra-high density mapping more rapidly and effectively identifies sites of breakthrough after initial RFA application. A larger study is planned to provide more insight. Conflict of Interest: None